Prachin va madyayugin bharatacha itihas XI arts - Gaikwad R.D., Bhosale R.H., Patil N.D. & etc. (Phadake Prakashan, Kolhapur, 2006)
History
MARATHI
Keywords: Prachin va madyayugin bharatacha itihas XI arts; History; History